PENGGUNAAN METODE ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PERJUANGAN PARA TOKOH MASA PENJAJAHAN JEPANG : Penelitian Tindakan Kelas pada Siswa Kelas V SD Negeri 3 Cikidang Kecamatan Lembang Kabupaten Bandung Barat - Irman Nurmansyah, - (2012)
This research is motivated by the findings of the field that the student learning outcomes in social studies on the material struggles of the characters in the Japanese colonial period is low, under the KKM with it's score is 60. The use of lecture method and recorded on a daily basis, making the learning becomes monotonous and makes students passive. Thus it is necessary for change to improve learning outcomes, student activities, as well as the creativity of teachers in managing the learning process is to apply the method of role playing. In this study using the method of Classroom Action Research (CAR) with the subject of a class V student of SDN 3 Cikidang Lembang district of West Bandung regency academic year 2011/2012 the number of students, it is consisting of 22 male students and 17 female students. This study is using three cycles, that each cycle consisting of planning, implementation, observation and reflection. There are two instruments used to collect data, those are test and the observation sheet. Planning to use the role playing method emphasizes the appreciation of each student in the role played by each character so the audience drawn into the atmosphere when the fighter against Japanese colonial rule. The results showed very satisfactory results, it looks from the students become more active and enthusiastic so that facilitate the teacher to teach of contents in learning. Post-test results in each cycle tends to increase. The average value of the I cycle 61 with 72% completeness, the second cycle reaches an average value of 68.1 with 87% the percentage of completeness, and the cycle III reached an average value of 78 to 95% the percentage of completeness. Thus the use of role playing method can improve student learning outcomes. The recommendations are based on the results of the study: first for the students are expected to be more active in learning, and dare to appear in front of the class, both for the teacher assessment of learning materials and the use of appropriate methods such as role playing method can assist teachers in achieving the goal of learning as well as providing opportunities for students to appear in front of the class, the third for schools to provide training using the method of role playing or other methods to improve the quality of learning, and the last for the next researcher to be more wise in using methods of allocation in the use of role playing.